2018
DOI: 10.1016/j.cpr.2017.11.002
|View full text |Cite|
|
Sign up to set email alerts
|

Intervention studies to foster resilience – A systematic review and proposal for a resilience framework in future intervention studies

Abstract: Psychological resilience refers to the phenomenon that many people are able to adapt to the challenges of life and maintain mental health despite exposure to adversity. This has stimulated research on training programs to foster psychological resilience. We evaluated concepts, methods and designs of 43 randomized controlled trials published between 1979 and 2014 which assessed the efficacy of such training programs and propose standards for future intervention research based on recent developments in the field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
336
0
18

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 446 publications
(423 citation statements)
references
References 67 publications
9
336
0
18
Order By: Relevance
“…with the goal of targeting resilience to achieve an end goal (eg, alleviating post-traumatic stress disorder), and (2) building resilience in clinical (eg, diabetes) and non-clinical populations (eg, corporate settings, college students) with the goal of preparing individuals for future generalized life stressors. [40][41][42] The only known intervention study targeting resilience in HIV examined a resilience intervention in PLWH in rural…”
Section: Covariatesmentioning
confidence: 99%
“…with the goal of targeting resilience to achieve an end goal (eg, alleviating post-traumatic stress disorder), and (2) building resilience in clinical (eg, diabetes) and non-clinical populations (eg, corporate settings, college students) with the goal of preparing individuals for future generalized life stressors. [40][41][42] The only known intervention study targeting resilience in HIV examined a resilience intervention in PLWH in rural…”
Section: Covariatesmentioning
confidence: 99%
“…Inclusion of resiliency assessment in paediatric rehabilitation echoes the paradigm shift toward a strength‐based, client‐centred care, as it encourages identification of clients' strengths and development of intervention plans to nurture clients' capacity for navigating though life's ups and downs (Chmitorz et al, ). Of the 41 studies that we identified, only five were intervention studies that assessed resiliency as outcome variables.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of looking at prospectively defined outcomes in resilience research has recently been highlighted [Chmitorz et al 2018]. While sample size was limited, we had the unique opportunity to explore genetic contributions to resilience in a prospective cohort where exposure to trauma was empirically measured.…”
Section: Discussionmentioning
confidence: 99%